Fungal Light-Oxygen-Voltage Domains for Optogenetic Control of Gene Expression and Flocculation in Yeast - Salinas-Sanhueza, F (American Society for Microbiology, 2018)
Optogenetic switches permit accurate control of gene expression upon light stimulation. These synthetic switches have become a powerful tool for gene regulation, allowing modulation of customized phenotypes, overcoming the obstacles of chemical inducers, and replacing their use by an inexpensive resource: light. In this work, we implemented FUN-LOV, an optogenetic switch based on the photon-regulated interaction of WC-1 and VVD, two LOV (light-oxygen-voltage) blue-light photoreceptors from the fungus Neurospora crassa. When tested in yeast, FUN-LOV yields light-controlled gene expression with exquisite temporal resolution and a broad dynamic range of over 1,300-fold, as measured by a luciferase reporter. We also tested the FUN-LOV switch for heterologous protein expression in Saccharomyces cerevisiae, where Western blot analysis confirmed strong induction upon light stimulation, surpassing by 2.5 times the levels achieved with a classic GAL4/galactose chemical-inducible system. Additionally, we utilized FUN-LOV to control the ability of yeast cells to flocculate. Light-controlled expression of the flocculin-encoding gene FLO1, by the FUN-LOV switch, yielded flocculation in light (FIL), whereas the light-controlled expression of the corepressor TUP1 provided flocculation in darkness (FID). Altogether, the results reveal the potential of the FUN-LOV optogenetic switch to control two biotechnologically relevant phenotypes such as heterologous protein expression and flocculation, paving the road for the engineering of new yeast strains for industrial applications. Importantly, FUN-LOV’s ability to accurately manipulate gene expression, with a high temporal dynamic range, can be exploited in the analysis of diverse biological processes in various organisms. IMPORTANCE Optogenetic switches are molecular devices which allow the control of different cellular processes by light, such as gene expression, providing a versatile alternative to chemical inducers. Here, we report a novel optogenetic switch (FUN-LOV) based on the LOV domain interaction of two blue-light photoreceptors (WC-1 and VVD) from the fungus N. crassa. In yeast cells, FUN-LOV allowed tight regulation of gene expression, with low background in darkness and a highly dynamic and potent control by light. We used FUN-LOV to optogenetically manipulate, in yeast, two biotechnologically relevant phenotypes, heterologous protein expression and flocculation, resulting in strains with potential industrial applications. Importantly, FUN-LOV can be implemented in diverse biological platforms to orthogonally control a multitude of cellular processes. © 2018 Salinas et al.